Smart sheba: an investigation on the effectiveness of integrating LLM enabled chatbots and using a user-centred design strategy to enhance user experience of older adults - Chisty, Sharfuddin Khan; Abbasi, Khaled Imtiaz; Afsana, Fairana; Shefa, Sanjida Afroz (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.